Generation and affirmation of clones utilizing gynogenesis as a part of Japanese fumble - Yongxin Yein; Estir I. Vin; Xioang V. E (Advances in Aquaculture and Fisheries Management, 2019)
Two homozygous clones of Japanese flounder were produced by the gynogenesis that suppresses the cleavage of the eggs in the mitosis and then blocks the extrusion of the second polar body in the meiosis. Microsatellite was used to identify the genetic status of maternal parents and their progenies. 21 polymorphic microsatellite markers were chosen, distributed at the distal region of the 16 linkage group. In this experiment, the two used maternal parents were completely heterozygous, while both mitotic gynogenetic diploids and their clone progenies were homozygous for each marker, demonstrating the successful development of clonin